PEMANFAATAN OPEN SOURCE OWNCLOUD SEBAGAI MEDIA PENYIMPANAN DATA BERBASIS CLOUD COMPUTING - Firmansyah Amin; LM. Fid Aksara; Sutardi Sutardi (semanTIK, 2019)
Cloud Computing technology can be a solution to overcome the problem of storing data on a computer that is often used by many people. One of them is the OwnCloud application service. OwnCloud is an open source software, which means that anyone can use it for free and change the contents of the service. With the concept of cloud storage, users who access OwnCloud must log in first to access data located in the cloud storage. By utilizing a WiFi network to access OwnCloud, all forms of data sharing and synchronization can be accessed on the features provided.Difficulties of staff, lecturers and students to share study program data become difficulties that hinder activities in the academic community. So the results of this study conclude that OwnCloud services can be an efficient solution in managing files if implemented on a centralized campus.Keywords—Cloud Computing, Cloud Storage, Storage, OwnCloudDOI : 10.5281/zenodo.3066822